Symptomatic Follicular Lymphoma: Complete Remission After Chemoimmunotherapy with Bendamustine–Rituximab - Wulyo Rajabto; Agnes Stephanie Harahap; Handy Nugraha Putra (Acta Medica Indonesiana)
Follicular lymphoma (FL) is the second most common non-Hodgkin lymphoma in Western countries after diffuse large B-cell lymphoma. Most patients with FL present with asymptomatic disease. Survival rates have been rising over time mainly due to advancing therapeutic strategies